A new mayfly species of Choroterpes (Choroterpes) Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from southern Western Ghats, India - Muthukatturaja, Marimuthu; Balasubramanian, Chellaiah (Zootaxa, 2022)
A new species of Choroterpes (Choroterpes) Eaton, 1881 is described based on nymphs from southern Western Ghats, Karnataka, India. Choroterpes (Choroterpes) kumaradhara sp. nov. can be distinguished from other Oriental species of Choroterpes s.str. by the following combination of characters: (i) median emargination of labrum deeply cleft (U-shaped) with few denticle-like protuberances; (ii) the lateral margin of mandibles with a cluster of thin, long setae medially; (iii) gill I single lamellate, basal half broader and tapered to apex; (iv) median projection of dorsal lamella of gills II–VII plate-like and markedly larger and longer than laterals, ventral lamella small, trifurcated and (v) abdominal segments II–IX with posterolateral spines progressively longer posteriorly. Distribution and habitat ecology of the new species are provided.